67x-3=-3+67x

Simple and best practice solution for 67x-3=-3+67x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67x-3=-3+67x equation:


Simplifying
67x + -3 = -3 + 67x

Reorder the terms:
-3 + 67x = -3 + 67x

Add '3' to each side of the equation.
-3 + 3 + 67x = -3 + 3 + 67x

Combine like terms: -3 + 3 = 0
0 + 67x = -3 + 3 + 67x
67x = -3 + 3 + 67x

Combine like terms: -3 + 3 = 0
67x = 0 + 67x
67x = 67x

Add '-67x' to each side of the equation.
67x + -67x = 67x + -67x

Combine like terms: 67x + -67x = 0
0 = 67x + -67x

Combine like terms: 67x + -67x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 27.5+2= | | 8-3x=2x-3 | | 4x^2-7x+5=-2x+4 | | n-2+1=15 | | 63x+28=-26+63x | | 46x^2+50x-12.5=0 | | 3w+6=36-6 | | 3(n-1)=12 | | .2b=16 | | x*2+46=5*x-11 | | -6x-8+8x=-7x+4 | | 75=x*2.51x | | 2(3x-5)=7x+1 | | 1x+8y=38.5 | | 5x+6-2x=-6+x | | x^2-9x-41=-3x-1 | | 8x+6+2(4x-7)= | | 13-2x=2x-3 | | -7x+9=-8x-3 | | 13x^2+6x-4=0 | | 200=x*2x | | 3t+4=t+-3 | | 3vx^2=24v | | -57x+62=17+22x | | 20x+10+30x-2+7x+1= | | 2m+1=17 | | 7+Y=18.2-Y | | 2x+2=57 | | 6+78x=39x+12 | | x^3-5x^2+7x+51=0 | | x^2+8x+19=7 | | 9y-13=35 |

Equations solver categories